Tradeoffs of microbial life history strategies drive the turnover of microbial-derived organic carbon in coastal saline soils - Ning, Qi; Chen, Lin; Li, Fang; Zhou, Guixiang; Zhang, Congzhi; Ma, Donghao; Zhang, Jiabao (Frontiers in Microbiology, 2023)
Stable soil organic carbon (SOC) formation in coastal saline soils is important to improve arable land quality and mitigate greenhouse gas emissions. However, how microbial life-history strategies and metabolic traits regulate SOC turnover in coastal saline soils remains unknown. Here, we investigated the effects of microbial life history strategy tradeoffs on microbial carbon use efficiency (CUE) and microbial-derived SOC formation using metagenomic sequencing technology in different salinity soils. The results showed that high-salinity is detrimental to microbial CUE and microbial-derived SOC formation. Moreover, the regulation of nutrients stoichiometry could not mitigate adverse effects of salt stress on microbial CUE, which indicated that microbial-derived SOC formation is independent of stoichiometry in high-salinity soil. Low-salinity soil is dominated by a high growth yield (Y) strategy, such as higher microbial biomass carbon and metabolic traits which are related to amino acid metabolism, carbohydrate metabolism, and cell processes. However, high-salinity soil is dominated by stress tolerance (S) (e.g., higher metabolic functions of homologous recombination, base excision repair, biofilm formation, extracellular polysaccharide biosynthesis, and osmolytes production) and resource acquisition (A) strategies (e.g., higher alkaline phosphatase activity, transporters, and flagellar assembly). These trade-offs of strategies implied that resource reallocation took place. The high-salinity soil microbes diverted investments away from growth yield to microbial survival and resource capture, thereby decreasing biomass turnover efficiency and impeding microbial-derived SOC formation. Moreover, altering the stoichiometry in low-salinity soil caused more investment in the A-strategy, such as the production of more β-glucosidase and β-N-acetyl-glucosaminidase, and increasing bacterial chemotaxis, which thereby reduced microbial-derived SOC formation. Our research reveals that shift the microbial community from S- and A- strategies to the Y-strategy is important to increase the microbial CUE, and thus enhance SOC turnover in coastal saline soils.